Flexural response and load capacity of reinforced concrete beams strengthened with reinforced mortar layer. (15th October 2021) - Alharthi, Y.M.; Emara, M.; Elamary, A.S.; Sharaky, I.A.
Highlights: Steel-bar reinforced-mortar layer (SBRML) method proposed to strengthen RC beams. Bearing-capacity efficiencies of up to 214% was achieved with SBRML. Large reinforcement area of SBRML lead to enhanced beam stiffness. Prediction model of yield / peak load during flexural failure was proposed. Abstract: Reinforced concrete (RC) elements can be strengthened using several techniques. Among these techniques are the externally bonded (EB), near-surface-mounted (NSM), textile-reinforced mortar (TRM), and ultra-high-performance concrete (UHPC). The NSM and EB methods are primarily based on the efficiency and thickness of the concrete cover, while the UHPC method demands excessive surface preparation. This study presents a new technique to strengthen RC beams using a limited steel-bar-reinforced mortar layer (SBRML). This method reduces the installation time and cost and combines the advantages of existing techniques. An experiment with eight concrete beams, one unstrengthened beam (CB), and seven strengthened beams is performed. The RC beams are tested until failure under a four-point bending load. The effect of the SBRML reinforcement area, internal reinforcement configuration, adhesive type, concrete cover condition (with or without), position (bottom or side), and application type (casting or bonding) on the failure mechanism and capacity of the RC beams are studied. The results show an increase in the bearing capacities of RC beams strengthened with epoxy-bonded SBRML and cast SBRML in the range of 152.5–213.9% and 122.7–158.1%, respectively, compared to those of CB. The values of yield and ultimate loads for RC beams strengthened with epoxy-bonded RML are analyzed. A numerical simulation is performed and verified against the experimental results. A parametric study was conducted to reveal the effect of fiber-reinforced polymer reinforced mortar layer FRP-RML on the behavior of the strengthened beams.